Advancements in Weed Detection with Deep Learning Models and Image Augmentation Techniques - T. Maneesha, T. Maneesha; Adithya, B. Eswar; Prakash, V. Chandra; T. Saketh, T. Saketh; Subramanyam, M Madhusudhana (Journal of Neonatal Surgery, 2025)
Deep-Learning is one of the potent technique for automating weed detection procedures. This study offers a thorough investigation of deep learning methods for weed identification, emphasizing training-models such as Convolutional-Neural Networks (CNN), Autoencoders & Vision-Transformers. Specifically, CNNs are skilled at identifying hierarchical complex features from high dimensional images, while Autoencoders facilitate unsupervised feature learning, and Vision transformers which uses the power Attention Neural Networks enable selective focus on relevant regions in images. We review recent developments, difficulties, and potential paths in utilizing these deep learning models for weed detection, highlighting how they could transform farming methods by facilitating accurate and timely weed management strategies. Dataset contain images of carrot and weed which contain 250 training images out of which 130 carrot plant images and 120 weed image. There is 70% testing images with RGB range of 0 to 255. As we have only small dataset to ensure the model's resilience various argumentation where applied like flipping – horizontal/vertical, Magnified Range, brightness, height shift range and width shift range.